Infant Spinal Anesthesia for Urologic Surgery in a Patient With Epidermolysis Bullosa - Alexander B. Froyshteter; Jillian A. Dibiase; Catherine M. Seager; Alina Lazar (Case Reports in Anesthesiology)
Infant spinal anesthesia presents a viable alternative to general anesthesia for short procedures below the umbilicus. This technique eliminates the need for airway instrumentation while preserving hemodynamic and respiratory parameters. Epidermolysis bullosa is a rare inherited genetic disorder marked by mucocutaneous fragility, erosions, ulcerations, and blister formation. Anesthesia management for patients with epidermolysis bullosa necessitates meticulous planning to minimize shearing stress on the skin and mucosa. This case report details the application of spinal anesthesia for an infant with epidermolysis bullosa for urologic surgery, highlighting special considerations for neuraxial block placement in this vulnerable population.